Breast cancer: Analysis of the mortality trend in women in the State of Pará-Brazil (Research, Society and Development, 2021)
Introduction: Breast cancer is the second most prevalent type of cancer in women, with an increasing number of deaths each year, despite having a high cure rate when diagnosed and treated early. In order to try to reduce the mortality rate, the Ministry of Health launched ordinance n°189/2014 which aims to establish the Reference Services for Breast Cancer Diagnosis, with specialized professionals and diagnostic services. However, it is difficult to offer all procedures, impacting the definitive diagnosis and consequent increase in mortality. Objective: To assess the trend in breast cancer mortality in Pará, between 2010 and 2018, based on data from the National Cancer Institute (INCA). Methodology: This is an observational, descriptive, retrospective and comparative study based on data available at INCA. Results: In the period from 2010 to 2018, in Pará there were 17.8 deaths/100 thousand inhabitants due to breast cancer, below the values observed comparatively in Brazil (27.7) and in the North region (19.1). However, in Belém, mortality was higher, with an average of 30 deaths/100 thousand inhabitants. In the comparison between the regions of Brazil, the mortality coefficient in the North region is above the others, with the following averages: Southeast 17.62; Northeast 11.16; South 17.62 and Midwest 12.68. Conclusion: The mortality rate from breast cancer in the North Region is above the rates in other regions of Brazil, with emphasis on the city of Belém-Pará, where the average mortality rate is above that recorded throughout the country.